The asymmetrical bank-client relationship Case of Algerian public banks (International Journal of Scientific Research and Management (IJSRM), 2021)
Asymmetric information remains one of the most crucial problems in finance, though many works have been produced since the first writings of Akerloff, Spence and Stiglitz and many others. The inequality of getting information causes many problems to entreprises, because the responsible needs all information to solve these problems and decides what solution should fulfil the purpose in vew. In this context, the information and communication technologies (ICT) play a dominant role for the spreading of information to different users and researchers. The present work is articulated around two main parts. The first deals with the theoretical aspects of asymmetric information. The second is an empirical approach realised using a sample of questions in Algerian public Banks. All the questions deal with the impact of asymmetric information on the banking activity.